The Preventive Role of Hydrogen-Rich Water in Thioacetamide-Induced Cholangiofibrosis in Rat Assessed by Automated Histological Classification - Li, Chaofu; Zhao, Xing; Gu, Xiaoqiang; Chen, Ying; Yu, Guanzhen (Frontiers in Pharmacology, 2021)
Background: Cholangiofibrosis is a controversial intrahepatic cholangial lesion that precedes the development of cholangiocarcinoma. Here, we demonstrate that molecular hydrogen (H2) can be used to effectively prevent cholangiofibrosis. Methods: The safety and quality of life (QOL) of rats was firstly evaluated. H2 was administered to rats subjected to thioacetamide (TAA)-induced cholangiofibrosis throughout the whole process. Then, rats were administrated with TAA for 3 months and then followed by H2 intervention. Rat livers were harvested and assessed by light microscopy and convolutional neural network. RNA-seq was performed to analyze the genetic changes in these animal models. Results: Continuous use of H2-rich water was safe and improved QOL.The incidence and average number of cholangiofibrosis in the liver were higher in the TAA group (100%, 12.0 ± 10.07) than that in the H2 group (57.1%, 2.86 ± 5.43). The AI algorithm revealed higher Alesion/Aliver in the TAA group (19.6% ± 9.01) than that in the H2 group (7.54% ± 11.0). RNA-seq analysis revealed that H2 results in a decline in glycolysis. Moreover, in the third experiment, the incidence of microscopic or suspicious tumors and the ratio of liver lesions was decreased after long-term use of H2 (12.5%, 0.57% ± 0.45) compared with untreated group (100%, 0.98% ± 0.73). A number of intestinal microbiota was changed after H2 usage, including clostridiaceae_1, ruminococcus, turicibacter, coriobacteriales, actinobacteria, and firmicutes_bacterium. Conclusion: Hydrogen-rich water protects against liver injury and cholangiofibrosis and improved quality of life partially through regulating the composition of intestinal flora.